(untitled) (The Review of Diabetic Studies, 2025)
Introduction: Respiratory and intensive care units are very complicated places where patients’ lives and their ability to get better rely on quick, correct, and well-coordinated actions. In important situations, working together across different fields is now necessary to provide care that is safe, effective, and focused on the person receiving it. The purpose of this study was to look at how working together across different medical fields helps improve results for patients in respiratory and intensive care units. The study focused on making healthcare more effective, better communication, and increasing how satisfied patients and their families are with the care they receive. Methods: A detailed review of existing research was done by searching several databases like PubMed, CINAHL, Scopus, and Google Scholar, and the studies included were published in the last fifteen years. Both types of research—qualitative and quantitative—were looked at, using words like “interdisciplinary collaboration,” “respiratory care,” and “intensive care units.” The analysis found main themes, problems, and what works well in how teams work together. Results showed that working together across different fields helps make better medical decisions, lowers the chance of mistakes, improves how well people talk to each other, and makes patients happier. It also helps healthcare providers by building resilience, trust between each other, and a sense of shared responsibility. Conclusion: Working together across different fields is very important in critical care, leading to better results for patients and making their care more personal and caring. Including teamwork in the ICU environment helps patients get better care and makes the healthcare system work more smoothly.